Quality of life and congenital heart defects: comparing parent and professional values. Issue 5 (31st May 2006) - Knowles, Rachel L; Griebsch, Ingolf; Bull, Catherine; Brown, Jacqueline; Wren, Christopher; Dezateux, Carol
Abstract : Objective: To compare preferences obtained from health professionals with those from parents for the longer-term health outcomes of children with congenital heart defects. Setting: Cardiology conference; hospital. Participants: 109 paediatric cardiology professionals (72% female, median age 38 years) and 106 parents of children with congenital heart defects (82% female, median age 37 years). Interventions: Eight health state descriptions, for cardiac and neurological disability resulting from congenital heart defects, were developed and presented with a self-administered anonymous questionnaire. Respondents were asked to rank health state descriptions from best to worst, score each health state using a visual analog scale and mark death on this scale. Results: Health professionals and parents agreed in the order of ranking health states from best to worst. Both groups assigned the lowest scores to health states with severe neurological disability. Scores did not differ significantly by age, sex or whether the respondent was in the health professional or parent group. Of all respondents, 8% (17) scored at least one health state description worse than death. Conclusions: Parents and health professionals place similar values on the quality of life outcomes of children with congenital heart defects. Both are more averse to health states describing worse neurological than cardiac disability. Improving our understanding of the relative importance of different outcomes to children and families is an important basis for sharing decisions about clinical care. The views of young people with congenital heart defects should be an important focus for future enquiry into health outcomes.